Using real-world patient experiences to inform point-of-care decisions and care management strategies in urothelial carcinoma. Issue 28 (1st October 2022) - Ackbarali, Tariqa; Chisolm, Stephanie; Gore, John L.; Meeks, Joshua J; Shore, Neal D.
Abstract : 280 Background: Approvals of targeted therapies and immune checkpoint inhibitors hold the promise of improving long-term survival in patients with urothelial carcinoma. Competence gaps that were identified prompted the design of a unique educational series for the urology-oncology team. Optimal management of urothelial carcinoma relies on effective patient-provider communication and decision-making. To provide an integrative learning experience, the patient voice was embedded into the clinical content through shared insights and patient-reported data. Methods: A 4-part CME series was launched live-online in October 2021 in partnership with the Large Urology Group Practice Association and remains on-demand through October 2022 at UroCareLive.com and OMedLive.com. A companion patient program was held in September 2021 in partnership with the Bladder Cancer Advocacy Network and remains on-demand at CancerCoachLive.com. Behavioral assessment of preferences and attitudes toward managing patients were examined throughout the CME series and patient/caregiver program. A planned analysis of the data from these questions will determine patient and clinical impact. Outcomes from the patient program were analyzed and presented during the CME series followed by expert-identified strategies to improve clinical practice. Results: To date, 775 clinicians and 15, 193 patients have participated in the educational initiative. Of the patient-reported experiences and preferences: 44% prefer to discuss benefits and risks of treatment options; and while 85% prefer to make decisions with their team, 67% felt overwhelmed and ultimately allowed their team to select therapy. Patient insights revealed challenges related to quality of life, side-effect management, and disease management. Patient-provider disparities were observed across preferences for point-of-care treatment discussions and quality of life challenges. Clinical and patient impact following integration of the patient voice will be analyzed. Conclusions: The initiative contributed to the provision of valuable patient insights and preferences based on real-world experience which were integrated into provider education. Increasing this awareness fostered practical strategies and discussion to improve patient-centered care. Education incorporating the patient voice into provider education can further sensitize clinicians to patient concerns and facilitate point-of-care decision-making.